Research Methods in the Study of Intersectionality in Psychology: Examples Informed by a Decade of Collaborative Work With Majority World Women’s Grassroots Activism - Grabe, Shelly (Frontiers in Psychology, 2020)
Very few theories have generated the kind of interdisciplinary and international engagement that marks the intellectual history of intersectionality, leaving some authors to suggest that intersectionality is the most important theoretical contribution that the field of women’s studies has made thus far. Yet, consideration of intersectionality as a research paradigm has yet to gain a wide foothold in mainstream psychology. The current article uses a program of multimethod research designed in partnership with, and intending to center the intersectional experiences of, majority world women to propose a research agenda for the empirical study of intersectionality. Specifically, it is suggested that a research agenda rooted in intersectional understandings requires that: 1) researchers think carefully about social categories of analysis and how their methodological choices can best answer those questions, 2) psychologists reposition their research questions to examine processes by which structural inequities lead to power imbalances and gender-based norms that sustain women’s experience of marginalization and oppression, and, 3) we understand how intersectional experiences can be applied toward change. Intersectional investigations hold a key to interrupting the structural dimensions of power that result in egregious consequences to peoples’ social, economic, and political lives, but only if we radically restructure what we think about knowledge, our roles, and the products of our research.